2019
DOI: 10.1108/mrjiam-02-2018-0817
|View full text |Cite
|
Sign up to set email alerts
|

Absorptive capacity and technology: influences on innovative firms

Abstract: Purpose The purpose of this paper is to analyze the relationship between agile production (flexible production technology) and absorptive capacity. Design/methodology/approach We use a database of 1,864 Spanish industrial firms from the Survey of Business Strategies (the largest Spanish database of its kind). Our theoretical approach is based on the resource-based view and the dynamic capabilities perspective. The methodology includes descriptive statistics analysis and lineal regression with moderator effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 31 publications
(36 reference statements)
0
14
0
Order By: Relevance
“…Furthermore, researchers investigated how organisations operating in a cluster can develop resilience or absorptive capacity. However, the focus was on organisations; there was no investigation on how being in a cluster can affect their resilience or absorptive capacity (Taslimi et al, 2020, Martinez-Sanchez et al, 2019. In other words, the focus is mainly on organisations, and relatively less is known on how being in a cluster (i.e.…”
Section: Empiricalmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, researchers investigated how organisations operating in a cluster can develop resilience or absorptive capacity. However, the focus was on organisations; there was no investigation on how being in a cluster can affect their resilience or absorptive capacity (Taslimi et al, 2020, Martinez-Sanchez et al, 2019. In other words, the focus is mainly on organisations, and relatively less is known on how being in a cluster (i.e.…”
Section: Empiricalmentioning
confidence: 99%
“…In other words, the focus is mainly on organisations, and relatively less is known on how being in a cluster (i.e. SCCDCs) may affect the cluster members' DCs (Martinez-Sanchez et al, 2019, Taslimi et al, 2020.…”
Section: Empiricalmentioning
confidence: 99%
“…This study demonstrates that emotionally hot constructs such as EC play an important role in the relationship between ITC and IP, because of improvements in information processing, the use of IT and in virtual communication. This finding is quite significant because it forces us to reconsider the relevance of continuing with studies that propose mediating factors in the relationship between ITC and IP, which imply an additional effort in terms of rational processing of information. This is what has been done so far in the literature with constructs such as strategic market orientation (Wang et al, 2013), the corporate entrepreneurship capacity (Chen et al, 2015) and absorptive capacity (Mao et al, 2020;Martinez-Sanchez et al, 2019;Wu et al, 2019). All this because there is a risk of accentuating the cognitive overload and increasing the levels of stress that lead employees to stop receiving and using information provided by IT services, which compromises the possibility of obtaining better results in innovation.…”
Section: Discussionmentioning
confidence: 83%
“…This issue has been addressed in the academic literature from the perspective of IT capabilities (ITC) and several studies have shown the positive effect of ICTs on IP because of the improvement in knowledge management and interorganizational communication and direct support to specific stages in the innovation process (Arias-Pérez et al, 2021b;Parida and Örtqvist, 2015). Additionally, it has recently been proven that this relationship is mediated by organizational factors requiring an additional effort in terms of information processing in a rational and analytical manner, including strategic market orientation (Wang et al, 2013), corporate entrepreneurship capability (Chen et al, 2015) and absorptive capacity (Mao et al, 2020;Martinez-Sanchez et al, 2019;Wu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the relationship of innovation and organizational management have been studied by Dabic et al [20] and Damanpour and Schneiderw [21]. In addition, studies by Angel et al [22] found that innovation positively affects performance. This indicates that although the use of innovation as one of the variables has been widely used, its use as a variable in the sports industry remains unclear.…”
Section: Introductionmentioning
confidence: 99%